PERBEDAAN KEYAKINAN MAHASISWA DAN HUBUNGANNYA DENGAN PRAKTIK PEMBELAJARAN DITINJAU DARI ADVERSITY QUOTIENT - Muhtarom Muhtarom (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This research explained prospective teacher beliefs and the relationship between beliefs and practice of learning mathematics in the classroom in terms of differences in adversity quotient (AQ). Three prospective teacher who each had different AQ, namely climber, camper and quitter, were the subjects in this research. This subject has good communication skills, has passed microteaching and has no experience in teaching mathematics in schools. The research data were collected through interviews and classroom observation. Two interviews and learning observations for each research subject were carried out to obtain credible research data. Videos from interviews and video practice of learning mathematics in class were played repeatedly to increase the researcher's persistence in obtaining research data. The data that had been obtained were coded, reduced, triangulated, and analyzed to describe beliefs and implementations of beliefs in learning practices. The results showed that there were differences in beliefs between climber, camper and quitter students. The beliefs held by each student are actually applied in the practice of learning mathematics in the classroom. This shows that there is a high degree of consistency between beliefs and the practice of learning carried out.